Budaya Betangkant Anak Dalam Suku Dayak Keninjal Sebagai Upaya Kontektualisasi Kasih Allah - H Herwinasastra (Evangelikal: Jurnal Teologi Injili dan Pembinaan Warga Jemaat)
The purpose of this paper is to analyze a culture of Betangkant Children of the Keninjal Dayak tribe as an effort to contextualize the good news. The study of the meaning and cultural aspects of raising children in an effort to apply the gospel or good news in the context of the life of the Dayak Keninjal community. Through the culture of Betangkant Children in the Keninjal tribe, Madyaraya Village gives meaning and an entrance to evangelism for Dayak Keninjal to accept Jesus Christ as Savior in his life and figure of a Father who loves His Son. God created humans with creativity to be cultured, and with the framework of human culture looking at God and accepting God's self-revelation through filters and a framework that was intact in culture. Sustainability of God's covenant relationship with His people in all times and in all contexts. The culmination of this agreement is the Lord Jesus, who brought a new covenant to His people.